Strategi peningkatan kemampuan membaca Al Qur'an di TPQ Darussalam Desa Bandung Kecamatan Kebumen - Indah Sukma Ningsih; Benny Kurniawan (Tarbi: Jurnal Ilmiah Mahasiswa, 2026)
Taman Pendidikan Al Qur'an (TPQ) is an institution or community group that organizes non-formal Islamic religious education that aims to provide teaching in reading the Qur'an from an early age, as well as understanding the basics of Islamic dinul in kindergarten, elementary school and / or madrasah ibtidaiyah (SD / MI) or college. The purpose of this study is to find out how teacher strategies in improving the ability to read the Qur'an of students and to find out the results of using teacher strategies in improving the ability to read the Qur'an of TPQ Darussalam students. This research is a type of field research using a qualitative descriptive approach. Data collection techniques with observation, interviews and documentation. Data validity techniques use source tringulation, adequacy of reviewers and attending research. The results showed that the strategies used by TPQ Darussalam teachers were 1) Getting used to reading prayers and short letters before learning began. 2) Familiarize the culture of queuing by compiling qira'ati or the Qur'an on the teacher's desk before learning begins. 3) Familiarize students to read the Qur'an with the rules of good and correct tajweed. 4) Familiarize students to write material that has been delivered by the teacher. 5) Call students to recite using props and recite individually. 6) Asr prayer in congregation. 7) Apply a culture of greetings to teachers.